2017
DOI: 10.22211/cejem/78088
|View full text |Cite
|
Sign up to set email alerts
|

Concerning the Shock Sensitivities of Certain Plastic Bonded Explosives Based on Attractive Cyclic Nitramines .

Abstract: Plastic bonded explosives (PBXs) based on ε-2, 4,6,8,10,4,6,8,10,1,3,3,3,5,3,5,3,4,imidazole (BCHMX) were prepared using a hydroxyl-terminated polybutadiene as a binder (HTPB) and cured with hexamethylene di-isocyanate (HMDI). Recently published data for analogous PBXs with a polyisobutylene binder (i.e. a C4 matrix) are also included. All of these PBXs were tested using the Small Scale Water Gap Test according to STANAG 4490, the results of which are directly proportional to the impact and friction sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 10 publications
(17 reference statements)
0
19
0
Order By: Relevance
“…The determined values of both electric spark and impact sensitivities depend on shape and size of crystals that might connect with dislocations in theses crystals. [8a], [8c], The new method can be valuable for reliable calculation of electric spark sensitivity of those nitramines where they have a wide range of reported impact sensitivities.…”
Section: Resultsmentioning
confidence: 99%
“…The determined values of both electric spark and impact sensitivities depend on shape and size of crystals that might connect with dislocations in theses crystals. [8a], [8c], The new method can be valuable for reliable calculation of electric spark sensitivity of those nitramines where they have a wide range of reported impact sensitivities.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that there is a linear relationship between the measurements of RDAD with the other methods for determination of the electric spark sensitivity . Details of this instrument were illustrated elsewhere , . Zeman et al, , have used two different instrument RDAD and ESZ KTTV for studying electric spark sensitivity.…”
Section: Introductionmentioning
confidence: 98%
“…Electric spark or electrostatic sensitivity of an energetic compound shows the degree of sensitivity to the electrostatic discharge. [2b] Since the reported electric spark sensitivity depends on the configuration of the electrodes and structure of circuit, different data may be achieved by various test specification of electrode energy . The experimental data with an instrument marked as RDAD were used for introducing suitable predictive methods because there are a large set of data for nitramines .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a thermoanalytical study of these PBXs was conducted by Yan et al [17][18][19] The penetration performance of the advanced nitramines has been studied, [20][21][22] while different relationships have been presented and discussed by Zeman et al [23][24][25][26] based on the reactivity and sensitivity of the studied PBXs. BCHMX as part of a low sensitivity composition was studied by Hussein et al [27][28][29] From the previously mentioned research, it was concluded that the polymeric matrices have a signicant inuence on the different explosive properties of the studied PBXs.…”
Section: Introductionmentioning
confidence: 99%